2021
DOI: 10.4269/ajtmh.20-0104
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Rickettsial Infection in the Municipality of Uramita, Colombia

Abstract: This study aimed to analyze epidemiological indicators related to seroprevalent and seroincident cases of spotted fever group rickettsiae (SFGR) and to identify housing conditions related to tick infestation. A prospective study (2016–2018) was conducted to examine rickettsial seropositivity in humans, domestic animals, and wild mammals in the municipality of Uramita, Antioquia, Colombia, where a previous Rickettsia rickettsii outbreak was reported from 2014 to 2015. The seroprevalence and its associated facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Rhipicephalus sanguineus s.l. has been evaluated in a couple studies in Colombia and has been found negative for R. rickettsii [ 42 , 43 ]. Infection rates have been found higher (20.7% prevalence) among A. mixtum collected horses [ 23 ].…”
Section: Molecular Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Rhipicephalus sanguineus s.l. has been evaluated in a couple studies in Colombia and has been found negative for R. rickettsii [ 42 , 43 ]. Infection rates have been found higher (20.7% prevalence) among A. mixtum collected horses [ 23 ].…”
Section: Molecular Evidencementioning
confidence: 99%
“…Veritable R. amblyommatis infection could be misdiagnosed with other Rickettsia spp. given the cross-reactivity on clinically available IFA slides [ 25 , 42 , 54 ]. Despite the historical belief that this species is an endosymbiont found in Amblyomma sp.…”
Section: Molecular Evidencementioning
confidence: 99%
“…We could not identify bacteria in ticks, 1 and no severe tickborne diseases have been reported in this area so far; however, in the northern part of Colombia, fatal cases of Rocky Mountain spotted fever have occurred. 6 This complimentary analysis of epidemiological risk factors for severe tick infestation emphasizes the continuing need for a holistic health approach that includes both veterinary and human health interventions.…”
Section: Most Members Of the Rural Population Live And Work Closelymentioning
confidence: 99%
“…We could not identify bacteria in ticks, 1 and no severe tickborne diseases have been reported in this area so far; however, in the northern part of Colombia, fatal cases of Rocky Mountain spotted fever have occurred. 6 This complimentary analysis of epidemiological risk factors for severe tick infestation emphasizes the continuing need for a holistic health approach that includes both veterinary and human health interventions.…”
mentioning
confidence: 99%
“…We could not identify bacteria in ticks, 1 and no severe tickborne diseases have been reported in this area so far; however, in the northern part of Colombia, fatal cases of Rocky Mountain spotted fever have occurred. 6 This complimentary analysis of epidemiological risk factors for severe tick infestation emphasizes the continuing need for a holistic health approach that includes both veterinary and human health interventions.At the time of the study in 2017, information handouts were distributed to households and local officials, with advice on tick control and prevention of tick bites such as regular bush and weed control (also within the communities), minimizing close contact with animals, and treating animals according to official local recommendations. Since 2017 tick infestations in humans and the cases of severe chronic pruritus have not been quantified again; however, according to observations of health officials, tick infestation of human environments has slightly decreased, while animals remain heavily infested.…”
mentioning
confidence: 99%